Pentingnya Peranan Masyarakat Menjaga Budaya dan Tradisi Bali Dalam Pengembangan Pariwisata - Permana, Made Arya Sandhy; Dewi, Luh Putu Putri Candra (STKIP AGAMA HINDU SINGARAJA, 2024)
This writing aims to find out the role of the Balinese people in maintaining culture and traditions in the development of Bali tourism as a form of increasing and awareness of the Balinese people in maintaining their culture and traditions. Researchers conducted observations on Balinese people which is classified as qualitative descriptive research. Researchers can conclude that the role of society in maintaining culture and traditions in the development of Bali tourism still needs to be improved, the entry of various types of tourists who have various different backgrounds to Bali can have an influence on the entry of foreign cultures into Bali. However, not most of these influences can be avoided or even rejected. What can be done is how to overcome this to keep Balinese culture and traditions strong and increasingly present in the world of tourism. The results of this research show that the role of society in maintaining culture and traditions in Bali tourism development is very important, because sustainable tourism development is, in principle, development that places humans as the subject of development